ANALISIS KAUSALITAS FAKTOR-FAKTOR PERTUMBUHAN EKONOMI DI INDONESIA - Yondri Fadhli; Syamsul Amar B; Alpon Satrianto (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
The purpose of this study is to find out: How far is the Causality Relationship between the Amount of Money Supply, Investment, Savings and Economic Growth in Indonesia. This type of research is descriptive and associative. The type of data is secondary data. This study uses Time series data from 2005 Q1-2018 Q4 using the Vector Auto Regression (VAR) and Vector Estimation Causality Model (VECM) approaches. The results of this study show that: (1) there is a causal relationship between the money supply and economic growth. (2) There is no causal relationship between Investment and Economic Growth in Indonesia. (3) There is no causal relationship between Economic Growth Savings in Indonesia, but there is a one-way relationship namely Economic Growth affecting Savings. Based on the results of this study, the authors advise the Government to keep the national economy more stable and in a healthy financial institution. This will be able to facilitate the circulation of money in the community so that economic activity grows well.